2006
DOI: 10.1002/art.21875
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to ribosomal P proteins: A potential serologic marker for lupus membranous glomerulonephritis

Abstract: Objective. To evaluate the relevance of antibodies to ribosomal P proteins (anti-P antibodies) in discriminating histopathologic patterns of lupus nephritis.Methods. The study group comprised 81 consecutive patients with systemic lupus erythematosus who underwent renal biopsy and for whom frozen serum was available at the time of biopsy. All biopsy specimens were reviewed in a blinded manner, according to the 2004 criteria of the International Society of Nephrology and the Renal Pathology Society. Anti-P antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 14 publications
2
20
1
2
Order By: Relevance
“…Our group has demonstrated in previous work, the association of anti-ribosomal P and lupus nephritis, more specifically with the histological features of membranous glomerulonephritis. 3 Anti-LPL antibodies were also described in systemic sclerosis, in fact, 35% of these patients can present such antibodies. In this disease, antibodies were also correlated to hypertriglyceridemia, but also to disease's activity measured by a longer extension of cutaneous fibrosis and a higher frequency of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our group has demonstrated in previous work, the association of anti-ribosomal P and lupus nephritis, more specifically with the histological features of membranous glomerulonephritis. 3 Anti-LPL antibodies were also described in systemic sclerosis, in fact, 35% of these patients can present such antibodies. In this disease, antibodies were also correlated to hypertriglyceridemia, but also to disease's activity measured by a longer extension of cutaneous fibrosis and a higher frequency of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…O anticorpo antidsDNA, presente em cerca de 40% dos casos, correlaciona-se com a atividade renal, e o anti-P ribossomal, presente em 10-20% dos pacientes, está associado a manifestações neuropsiquiátricas e renais. [1][2][3] Pela paucidade desses marcadores, a busca de novos anticorpos que se correlacionem com atividade do LES seria de grande auxílio para a clínica.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…We read with interest the recent article by do Nascimento et al (1), in which they introduced antibodies to ribosomal P proteins as a novel marker for membranous lupus glomerulonephritis. Those investigators suggested that the presence of isolated anti-ribosomal P antibodies may discriminate patients with pure class V lupus nephritis, and that testing for these antibodies may be of clinical aid.…”
Section: To the Editormentioning
confidence: 99%
“…A maior frequência de cirrose no grupo anti-P positivo reforça o potencial papel patogênico desse anticorpo no fígado, assim como nas manifestações psiquiátricas no LES 29 , na nefrite lúpica 30,31 e na hepatite associada ao LES 12,16,32 . Estudos prévios demonstraram a presença da proteína ribossomal P0 em células de hepatoma 33 e a habilidade do anti-P penetrar nestas células e causar disfunção celular 14 .…”
Section: Características Clínicas E Laboratoriais Dos Pacientes Com Hunclassified